Role of necroptosis and immune infiltration in preeclampsia: novel insights from bioinformatics analyses - Lidan He; Feng Zhan; Lin Lu; Xia Zhang; Jianbo Wu (BMC Pregnancy and Childbirth, 2023)
Abstract Background Preeclampsia (PE) is a serious pregnancy complication that can adversely affect the mother and fetus. Necroptosis is a recently discovered new form of programmed cell death involved in the pathological process of various pregnancy complications. Our study aimed to identify the necroptosis-related differentially expressed genes (NRDEGs), create a diagnosis model and related disease subtypes model based on these genes, and further investigate their relationship with immune infiltration. Methods In this study, we identified NRDEGs by analyzing data from various databases, including Molecular Signatures, GeneCards, and Gene Expression Omnibus (GEO). Using minor absolute shrinkage and selection operator (LASSO) and logistic Cox regression analysis, we developed a novel PE diagnosis model based on NRDEGs. Furthermore, we developed PE subtype models using consensus clustering analysis based on key gene modules screened out by weighted correlation network analysis (WGCNA). Finally, we identified the difference in immune infiltration between the PE and control groups as well as between both PE subtypes by analyzing the immune cell infiltration across combined datasets and PE datasets. Results Our study discovered that the necroptosis pathway was significantly enriched and active in PE samples. We identified nine NRDEGs that involved in this pathway, including BRAF, PAWR, USP22, SYNCRIP, KRT86, MERTK, BAP1, CXCL5, and STK38. Additionally, we developed a diagnostic model based on a regression model including six NRDEGs and identified two PE subtypes: Cluster1 and Cluster2, based on key module genes. Furthermore, correlation analysis showed that the abundance of immune cell infiltration was related to necroptosis genes and PE disease subtypes. Conclusion According to the present study, necroptosis is a phenomenon that occurs in PE and is connected to immune cell infiltration. This result suggests that necroptosis and immune-related factors may be the underlying mechanisms of PE pathophysiology. This study opens new avenues for future research into PE's pathogenesis and treatment options.